Implementasi Pengurangan Sampah Organik Melalui Gerakan Peduli Kebersihan dan Pengolahan Sampah Mandiri di Wilayah Kelurahan Pulo Gadung Tahun 2024 - Agus Erwin; Euis Komalawati (Reformasi Administrasi, 2025)
Population density, economic growth, and changing consumption patterns drive the high volume of urban waste. Pulo Gadung Subdistrict is one of the subdistricts located in East Jakarta, with a daily waste generation of 25.6 tons, totaling 770 tons of waste per month. To address the waste issues in Pulo Gadung, the local government has implemented a program to reduce organic waste through a cleanliness awareness movement and independent waste management. The purpose of this study is to analyze and evaluate the implementation, challenges, and efforts to overcome challenges in organic waste reduction through the cleanliness awareness movement and independent waste management in Pulo Gadung Subdistrict. The research approach used is qualitative, with data collected through observation, questionnaires, and interviews. The research method employed is descriptive qualitative analysis. The results of the study indicate that this program has been running well, despite facing significant challenges such as low public awareness, limited resources, and ineffective coordination among the involved parties. The local government has made efforts to address these challenges through various initiatives, including educational campaigns, training, and the provision of composting facilities. However, the main obstacle faced is the low participation of the public in sorting and processing organic waste. Additionally, limited human resources, budget constraints, and weak oversight have been contributing factors. To overcome these barriers, Pulo Gadung Subdistrict has implemented comprehensive measures, including raising public awareness, strengthening human resource capacity, and improving coordination among relevant parties. The program demonstrates a strong commitment from the local government to succeed in reducing organic waste, but its success requires improvements in oversight and law enforcement.